The Effect of Feeding Various Limestone Particle Sizes, Limestone Solubility and Calcium Intake on Bone Status and Shell Quality of a Commercial White Layer Strain from 18-65 Weeks of age - Zhang, Bingfan; Weil, Jordan; Guerra, Antonio Beita; Maharjan, Pramir; Hilton, Katie; Suesuttajit, Nawin; Coon , Craig N. (International Journal of Poultry Science, 2019)
Background and Objective: The daily requirement of calcium for Commercial White laying hens has been steadily increasing for the past five decades because primary breeders have genetically annualized an increase in egg numbers. The objective of the study was to determine if Commercial White laying hens (from 18-65 week of age) require different dietary levels of soluble and insoluble calcium than older layers. Materials and Methods: One hundred and ninety two,18 week old, Commercial White laying hens were housed in group wire cages with four layers per unit and randomly assigned into a 2×2 factorial arrangement (2 predicted Ca intakes hen–1 day–1 and 2 limestone sources with different in vitro solubility) to provide 12 replicate units per treatment. Hen day egg production (HDEP), egg weight (EW), egg mass (EM), feed intake (FI), body weight (BW), specific gravity (SG), shell weight per unit surface area (SWUSA), bone ash concentration (AC) and bone breaking force (BBF) were determined throughout the 47 week feeding study. Results: Commercial White laying hens consuming 5 g calcium hen–1 day–1 with an in vitro lower solubility of 35.8% produced eggs with a significant increase in egg specific gravity and Shell Weight per Unit Surface Area (SWUSA) compared to hens consuming 3.56 g hen–1 day–1 during a 47 week production period. Bone size was not affected by solubility, Ca intake or age; however, bone ash concentration (AC) and bone breaking force (BBF) were increased from 18 week of age to ~40/50 week of age. The AC and BBF of the Commercial White laying hens decreased during the later portion of the production period (50-64 week) especially when the daily consumption was only3.56 g Ca from limestone with higher in vitro solubility of 49.4%. The AC and BBF showed that 3.56 g daily Ca intake with 49.4% solubility for 18-65 wk Commercial White laying hens was not sufficient to maintain bone status of hens after 50 week. Conclusion: The results support the idea that both osteoclastic and osteoblastic activities are present in the bone after sexual maturity. Bone strength and bone ash content of Commercial White laying hens(18-65 week) were maintained or improved by feeding hens increased quantities of a lower soluble Ca limestone to reduce Ca mobilization from medullary and cortical bone for egg shell formation. Hens (18-65 week) consuming 5 g of the lower soluble Ca limestone produced significantly higher shell quality than hens consuming 3.5 g hen–1 day–1.